2014
DOI: 10.1071/rd13012
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of naturally occurring regulatory T lymphocytes in blood of mares with early pregnancy loss

Abstract: Early pregnancy loss is a major reason for low reproductive efficiency in the horse. In humans and mice, low numbers of regulatory T cells (Treg cells) are linked to miscarriage. The percentage of Treg cells in oestrous mares at the start of the breeding season was evaluated in relation to the outcome of subsequent pregnancy. For identification and quantification of Treg cells, a highly sensitive and specific qPCR assay targeting the Treg-specific demethylated region in the equine forkhead box transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In humans, Tregs were decreased in peripheral blood and decidua in women with miscarriages and an impaired suppressive capability of Tregs in recurrent miscarriage cases was also observed (Tsuda et al 2019). Furthermore, early pregnancy loss correlated with a low level of naturally occurring Tregs in mares (Aurich et al 2014). Taken together, these observations indicate that equine PSGs, like human and murine PSGs, may play a role in the generation of Tregs via activation of TGFB, and therefore are important to maintain immune tolerance during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, Tregs were decreased in peripheral blood and decidua in women with miscarriages and an impaired suppressive capability of Tregs in recurrent miscarriage cases was also observed (Tsuda et al 2019). Furthermore, early pregnancy loss correlated with a low level of naturally occurring Tregs in mares (Aurich et al 2014). Taken together, these observations indicate that equine PSGs, like human and murine PSGs, may play a role in the generation of Tregs via activation of TGFB, and therefore are important to maintain immune tolerance during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…In mares, the embryo descends around day 6 to 7 of pregnancy, and implantation starts 10 days later. However, a lower level of peripheral CD4 + FOXP3 + Tregs was noted in mares that experience early pregnancy loss [ 31 ]. A similar phenomenon was observed in women enduring recurrent spontaneous abortion [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest two possible hypotheses. First, during the short post-insemination period (24 h), the expansion of uterine Tregs might be limited only to local lymph nodes, or Tregs percentage increases significantly and rapidly only in response to pregnancy, presumably due to fetal antigen and hormone stimulation, as suggested by others [ 5 , 31 , 32 ]. Our results showed that the percentage of CD4 + FOXP3 + lymphocytes is similar during the estrous cycle to that around the endometrial cups, that is, during pregnancy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infiltrating cells include a higher percentage of FOXP3 + CD4 + T-regulatory cells relative to peripheral blood [ 23 ]. Mares with early pregnancy loss have lower levels of peripheral blood T-regulatory cells [ 22 ]. It is reasonable to hypothesize that memory T-regulatory cells generated in response to our primary transplant ensured early survival of the MHC-I-positive secondary transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Lifespan could be decreased by accelerated immune destruction from a memory response, as observed in serial ectopic transplant studies in mice [ 19 ], or become longer, as observed in male skin grafting experiments in mice in which recipients' immune systems were primed by multiple syngeneic pregnancies [ 20 ]. The latter could occur as a result of regulatory T-lymphocyte memory [ 21 23 ] or other mechanisms of induced tolerance, such as T-cell exhaustion resulting from prolonged antigen exposure [ 24 ].…”
Section: Introductionmentioning
confidence: 99%